Influência de fatores sociais individuais e comunitários na qualidade de vida relacionada a saúde bucal de crianças: uma coorte de 7 anos - Knorst, Jessica Klöckner (2018)
Lately, oral health inequalities studies have approached a new perspective. In this perspective, patient-reported health outcomes, such as oral health self-perception and oral health-related quality of life (OHRQoL), have been used. OHRQoL is an important outcome that results from the interaction between oral health conditions, general health, individual, social and contextual factors. Several studies have highlighted the importance of assessing the characteristics of social life and the role of social deprivation on OHRQoL. However, most of these studies have a cross-sectional design, which limits cause-effect relationship. Considering that childhood characteristics may reflect throughout adult life, the purpose of this study is to evaluate the influence of neighborhood and individual social factors on children‘s OHRQoL . This cohort study assessed 639 children (1–5 years old) during a survey in 2010 in the city of Santa Maria, RS, Brazil. In the seven years follow-up, all subjects were again invited to participate in the study, and a total of 449 children (response rate of 70.3%) were re-evaluated. OHRQoL was assessed at follow-up through the Brazilian version of the Child Perception Questionnaire (CPQ 8-10). Exploratory variables were collected during the baseline and included: presence of class association, workers association and cultural community centers (contextual level); individual social networks; sociodemographic variables and oral health measures. Multilevel Poisson regression model was used to investigate the influence of individual and contextual characteristics on OHRQoL. The mean age of children evaluated at follow-up was 10 (standard deviation; 1.4) years. Children who lived in areas with class associations at baseline reported better OHRQoL at follow-up (IRR 0.82; 95 % CI 0.72-0.94). Regarding individual variables, female sex, low socioeconomic level, abcense of parental involvement at school activities, attending a dentist by toothache and accentuated overjet were also associated with higher overall CPQ8-10 scores. The individual and neighborhood social capital influenced on OHRQoL. Children who lived in neighborhoods with higher social capital and whose parents had higher levels of individual social networks presented a better OHRQoL. This knowledge is important in the planning of public health policies to improve the health and well-being of children. It may give policy makers useful insights about the importance of community and social relations, helping to improve OHRQoL throughout life-course.